Rare Light : J. Alden Weir in Windham, Connecticut, 1882-1919 - Dawson, Anne E. (Anne Elizabeth), 1956- (Book collections on Project MUSE., 2016)
Chronicling the artist's life in Connecticut's "Quiet Corner."